2011
DOI: 10.1016/j.ijdevneu.2011.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol‐induced neuronal death in central extended amygdala and pyriform cortex during the postnatal period of the rat

Abstract: Mothers who consume alcohol during pregnancy may cause a neurotoxic syndrome defined as fetal alcohol spectrum disorder (FASD) in their offspring. This disorder is characterized by reduction in brain size, cognitive deficits and emotional/social disturbances. These alterations are thought to be caused by an alcohol-induced increase in apoptosis during neurodevelopment. Little is known about neuroapoptosis in the central extended amygdala and the pyriform cortex, which are key structures in emotional/social beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…Therefore, this stage of development remains a window of plasticity during which structures remain vulnerable to cytotoxic insults that can destabilize subsequent circuit performance. Our observations in olfacto-hippocampal circuit dysfunction may be associated with the immediate wave of neurodegeneration observed throughout this circuit following acute ethanol exposure, as detected by caspase-3 and caspase-9a activation [116]. Just as with our studies, Criado and Ehlers [36] found that hippocampal event related oscillations in adult rats exposed to ethanol as adolescents were elevated at specific frequency ranges, again suggesting a possible shift in excitation/inhibition balance.…”
Section: Findings Of Neuropathology In Acute Ethanol Exposure Animsupporting
confidence: 76%
“…Therefore, this stage of development remains a window of plasticity during which structures remain vulnerable to cytotoxic insults that can destabilize subsequent circuit performance. Our observations in olfacto-hippocampal circuit dysfunction may be associated with the immediate wave of neurodegeneration observed throughout this circuit following acute ethanol exposure, as detected by caspase-3 and caspase-9a activation [116]. Just as with our studies, Criado and Ehlers [36] found that hippocampal event related oscillations in adult rats exposed to ethanol as adolescents were elevated at specific frequency ranges, again suggesting a possible shift in excitation/inhibition balance.…”
Section: Findings Of Neuropathology In Acute Ethanol Exposure Animsupporting
confidence: 76%
“…There was also a main effect of age, ([age] PCX F [1,24] =4.75, p=0.0394) with no significant interaction between treatment and age. Neurodegeneration in the PCX has been detected before immediately following acute ethanol exposure in early postnatal rats (Balaszczuk et al, 2011) and in adult rats (Leasure and Nixon, 2010). The identity of the affected cell populations and long-term effects however, had not previously been identified.…”
Section: Resultsmentioning
confidence: 99%
“…Such damage may contribute to the impaired impulse control and social deficits observed in children with FASD throughout life. In particular, rodent models of developmental alcohol exposure result in increased caspase-3 expression in the central nucleus of the amygdala (Mitchell & Snyder-Keller, 2003), long-term reductions to amygdalar opioid signaling (Lugo, Wilson, & Kelly, 2006), and altered synaptic connectivity and neuronal loss in the amygdala (Balaszczuk, Bender, Pereno, & Beltramino, 2011; Cullen et al, 2013; Zhou et al, 2010) and the prefrontal cortex (Hamilton, Whitcher, & Klintsova, 2010; Ikonomidou et al, 2000; Lawrence, Otero, & Kelly, 2012; Whitcher & Klintsova, 2008). Dysfunction of these brain areas could contribute to disruptions in social and play behavior observed in AE rats.…”
Section: Discussionmentioning
confidence: 99%